Thematic charting of military chaplaincy scholarship (2014–2024) - Hazemali, David (Bogoslovni vestnik, 2025)
This scoping review maps peer-reviewed scholarship on military chapla-incy (2014–2024) indexed in Scopus and Web of Science. We asked how cha-plains’ roles, delivery models, collaborations, and methodological approaches relate to moral injury, suicide care, religious and ethnic plurality, and readiness.Searches (14 March 2025) yielded 217 records and after analysis 58 met our criteria analysis. We classified studies as outcomes (n=3), implementation/pro-vider-facing (n=37), and conceptual/historical/policy/evidence syntheses(n=18). The literature depicts a maturing discipline, moving from traditional ad hoc pastoral responses towards structured, reproducible approaches. Military Chaplain collaboration with behavioural health and command is the most de-veloped thematic area, supported by learning collaboratives and crisis proto-cols. Moral-injury interventions cluster into chaplain-only, co-facilitated, and protocolised narrative-ritual models, with promising but limited outcome si-gnals. Evidence-informed practice is growing via screening, shared language, and brief interventions; comparative work highlights diverse measurementapproaches, ethics, and governance across countries. Samples are heavily we-ighted toward Christian chaplains, male service members, and the U.S. VA/DoD contexts. Gaps include rigorous trials, non-U.S. and minority-faith contexts, mechanism testing, and economic evaluation
Keywords: armed forces; confidentiality; duhovna pripravljenost; implementacijska znanost; implementation science; integrated care; integrirana oskrba; international comparison; mednarodna primerjava; military chaplaincy; military chaplains; moral injury; moralna rana; oborožene sile; preprečevanje samomora; scoping review; sistematični pregled literature; spiritual readiness; suicide prevention; vojaška duhovščina; vojaški kaplani; zaupnost